2021
DOI: 10.3389/fmed.2021.689114
|View full text |Cite
|
Sign up to set email alerts
|

Patient Preferences for Lung Cancer Treatments: A Study Protocol for a Preference Survey Using Discrete Choice Experiment and Swing Weighting

Abstract: Background: Advanced treatment options for non-small cell lung cancer (NSCLC) consist of immunotherapy, chemotherapy, or a combination of both. Decisions surrounding NSCLC can be considered as preference-sensitive because multiple treatments exist that vary in terms of mode of administration, treatment schedules, and benefit–risk profiles. As part of the IMI PREFER project, we developed a protocol for an online preference survey for NSCLC patients exploring differences in preferences according to patient chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Details on the study design have been published elsewhere. 39 , 40 This case study was identified as suitable for the comparison of DCE and SW-DR due to the potentially fragile physical state or diminished cognitive status of the patients. 41 44 The current study included DCE and SW exercises in the ways these methods typically would be applied to answer a particular clinical research question.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Details on the study design have been published elsewhere. 39 , 40 This case study was identified as suitable for the comparison of DCE and SW-DR due to the potentially fragile physical state or diminished cognitive status of the patients. 41 44 The current study included DCE and SW exercises in the ways these methods typically would be applied to answer a particular clinical research question.…”
Section: Methodsmentioning
confidence: 99%
“…Respondents were selected and referred to the PREFER research team by the treating oncologists at cancer treatment centers in Belgium and in Italy. 40 To be eligible, patients had to understand Italian or Dutch, be 18 y or older, and have a histologic or cytologic diagnosis of NSCLC as evaluated by clinicians. Patients were not eligible if they (as evaluated by the clinician): 1) had cognitive impairments rendering the participant incapable of informed consent or 2) were unable to understand the study materials.…”
Section: Methodsmentioning
confidence: 99%
“…Participants were selected and referred to the PREFER research team by the treating oncologists at the Thoracic Oncology Division of the European Institute of Oncology and the National Cancer Institute in Milan, and at the Respiratory Oncology Department of the KU Leuven University Hospital in Leuven. Patients were eligible if they were stage I to IV NSCLC patients, over 18 years of age, and able to read and speak Italian or Dutch ( Monzani et al, 2021 ). Patients were approached via phone or in the hospital waiting room before a visit, and if they agreed to participate, they received the information sheet and a consent form by email.…”
Section: Methodsmentioning
confidence: 99%
“…This case study involved a large cohort of patients with NSCLC at stages from I to IV recruited from three cancer treatment centers across Italy and Belgium. 8 The clinical aim of this case study was to assess how patients trade-off benefits and risks related to treatment alternatives, by using both discrete choice experiment (DCE) and swing weighting (SW) methods. DCE asks respondents to make choices among sets of profiles in a series of choice questions, with different levels of benefits and risks associated with the choices.…”
Section: Overviewmentioning
confidence: 99%
“…Due to the SARS-CoV-2 pandemic, the original protocol of the PREFER lung cancer quantitative case study 8 had to be modified. Originally, the protocol specified that eligible NSCLC participants could be contacted either by phone or approached in the waiting room either before or after a medical visit, at which point the researcher would introduce the study.…”
Section: A Web-based Implementation Of Preference Surveys In An Elderly and Diseased Populationmentioning
confidence: 99%